House Price Developments in Europe : A Comparison - Hilbers, Paul (IMF Working Papers; Working Paper, 2008)
House prices in Europe have shown diverging trends, and this paper seeks to explain these differences by analyzing three groups of countries: the "fast lane", the average performers, and the slow movers. Price movements in the first two groups are found to be driven mostly by income and trends in user costs, and housing markets in these countries seem relatively more susceptible to adverse developments in fundamentals. Real house price declines among the slow movers are harder to explain, although ample supply, low home ownership, and less complete mortgage markets are likely factors. The impact of macroeconomic, prudential and structural policies on housing markets can be large and should be a factor in policy decisions.